Incidental extramammary findings on breast magnetic resonance imaging: Prevalence and recommended diagnostic follow-up - Jaber Hussain Alsalah (PLoS ONE, 2025)
Among the current clinical imaging modalities, magnetic resonance imaging (MRI) has the highest sensitivity for breast cancer detection. Only a few studies have been conducted on the extramammary findings of breast MRI; nonetheless, incidental extramammary findings on the breast MR images of the patients are likely to be malignant and may influence staging and treatment. The aim of this study was to assess the prevalence of extramammary findings on breast MRIs and explore the appropriate diagnostic steps. This retrospective study included 234 patients (mean age: 55.8 years) who underwent breast MRI scans at King Abdul-Aziz University Hospital between 2013 and 2020. Reports were reviewed to identify incidental findings, categorized as pathological findings or congenital anomalies. The included patients had confirmed malignant tumors and no prior breast MRI findings. The patient demographics, MRI findings, and indications were recorded. Nineteen incidental extramammary findings were recorded in 16 of the 234 patients with breast cancer whose records were reviewed. The most common sites were the musculoskeletal system (21%), liver (37%), and lungs (21%). Pleural and chest wall involvement was found in two instances (10.5%). One patient (6%) underwent a biopsy, while 15 patients (94%) underwent further imaging. Incidental extra-mammary findings on breast MRI should not be neglected. This study showed that breast MRI examinations were associated with a 7% rate of extramammary findings, suggesting the need for careful evaluation during routine breast MRI. These findings may require further diagnostic evaluation depending on the clinical context. A consistent and systematic diagnostic approach is needed to identify extramammary abnormalities on breast MR scans.